The development of the microsporidium Paranosema (Nosema) locustae for grasshopper control: John Henry’s innovation with worldwide lasting impacts - Lange, Carlos Ernesto (2017)
In this issue of “Protistology” we bring a tribute to the Society for Invertebrate Pathology (SIP) that this year celebrated its 50th anniversary. The SIP have been always playing an important and global role in studies on unicellular eukaryotic symbionts of invertebrates, in particular on microsporidia. The Microsporidia Division was established in 1970 (see the Table 1) as the first official division of the SIP, and most of researchers in the field of Microsporidiology have been SIP members and published in the Journal of Invertebrate Pathology, an official publishing organ of the Society. Beneath we provide a table with some major landmarks of the SIP history. In this issue we also publish the paper prepared by Dr. John Henry, an outstanding scholar in the fields of insect pathology, microbiological control, and microsporidia research, who developed the only one commercially successful biological insecticide based on microsporidian spores. His paper includes the materials presented at the Microsporidia Division symposium “The past and future frontiers in microsporidiology” at the 50th Annual Golden Jubilee Meeting of the Society for Invertebrate Pathology.